Using a risk assessment framework to spatially and temporally spread the fishery catch limit for Antarctic krill in the west Antarctic Peninsula: A template for krill fisheries elsewhere - Warwick-Evans, V.; Constable, A.; Dalla Rosa, L.; Secchi, E. R.; Seyboth, E.; Trathan, P. N. (Frontiers in Marine Science, 2022)
The west Antarctic Peninsula is an important breeding and foraging location for marine predators that consume Antarctic Krill (Euphasia superba). It is also an important focus for the commercial fishery for Antarctic krill, managed by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). Aiming to minimise ecosystem risks from fishing, whilst enabling a sustainable fishery, CCAMLR has recently endorsed a new management framework that incorporates information about krill biomass estimates, sustainable harvest rates and a risk assessment to spatially and temporally distribute catch limits. We have applied a risk assessment framework to the west Antarctic Peninsula region (Subarea 48.1), with the aim of identifying the most appropriate management units by which to spatially and temporally distribute the local krill catch limit. We use the best data currently available for implementing the approach, recognising the framework is flexible and can accommodate new data, when available, to improve future estimates of risk. We evaluated 36 catch distribution scenarios for managing the fishery and provide advice about the scale at which the krill fishery can be managed. We show that the spatial distribution with which the fishery currently operates presents some of the highest risks of all scenarios evaluated. We highlight important issues that should be resolved, including data gaps, uncertainty and incorporating ecosystem dynamics. We emphasize that for the risk assessment to provide robust estimates of risk, it is important that the management units are at a similar scale to ecosystem function. Managing the fishery at small scales has the lowest risk but may necessitate a high level of management interaction. Our results offer advice to CCAMLR about near-term management and this approach could provide a template for the rest of the southwest Atlantic (Area 48), or fisheries elsewhere. As each data layer influences the outcome of the risk assessment, we recommend that updated estimates of the distribution, abundance and consumption of krill, and estimates of available krill biomass will be key as CCAMLR moves forward to develop a longer-term management strategy.